Ontology-based Chatbot to Support Monitoring of Server Performance and Security By Rule-base - Fauzan Ishlakhuddin; Azhari SN (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2021)
The server is a computer program or a device that provides functionality for other programs or devices, called "clients". Generally, server computers have many resources that can be used by one or more clients through the network with specific permissions and requirements. Therefore, the server needs a monitoring system that can monitor server activity and notify if problems occur. This research focuses on developing a notification and question and answer system to connect the network admin with the monitoring system via chatbot. The developed chatbot can send notifications to the admin if an error occurs and can answer questions about the server's condition. The question and answer system developed implements natural language processing for Indonesian. The process of understanding questions is by classifying each word (token) based on language knowledge stored in the ontology. Then the classification results are processed by rule-base to produce conclusions to take monitoring data and compiled into answers. The test results show that the developed system can auto-notify if any problem in a server, and can answer questions by accuracy 95%.